2020
DOI: 10.1111/trf.15967
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of allotype “b” in human platelet antigen 1 to 29 systems among blood donors in Japan estimated using high‐resolution melt analysis

Abstract: Background: Antibodies against human platelet antigens (HPAs) cause thrombocytopenias. It is thus important to know the frequency of "b" allotypes in each HPA system for the diagnosis and treatment of anti-HPA antibodymediated thrombocytopenia. Study Design and Methods: Genomic DNA was extracted from peripheral blood cells obtained from 2170 blood donors in Japan and was subjected to highresolution melt (HRM) analysis using polymerase chain reaction for each of the HPA genes, using 23 primer pairs. For genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The relative frequency of the HPA-1b allele was 0.4% in Japan. Therefore, the HPA-1b/1b phenotype was calculated to be <0.002% in the Japanese population, 15 and there was no suitable blood donor in the Japanese Red Cross Society (JRC) registry. Written informed consent was obtained from the patient.…”
Section: Methodsmentioning
confidence: 99%
“…The relative frequency of the HPA-1b allele was 0.4% in Japan. Therefore, the HPA-1b/1b phenotype was calculated to be <0.002% in the Japanese population, 15 and there was no suitable blood donor in the Japanese Red Cross Society (JRC) registry. Written informed consent was obtained from the patient.…”
Section: Methodsmentioning
confidence: 99%
“…45 One of the newly developed assays, PCR-HRM, is faster and more costeffective than PCR-SSP but requires expensive, specialized equipment. 44 In Japan, bead-based multiplex PCR-SSO is the most widely used method because it can genotype multiple HPAs in a single well and is commercially available.…”
Section: Genotyping Platformsmentioning
confidence: 99%
“…A number of genotyping platforms have been developed for HPA‐15, including: sequence‐specific primer polymerase chain reaction (PCR‐SSP), 5 restriction fragment length pattern PCR (PCR‐RFLP), 5 real‐time PCR, 5 melting curve analysis, 35 sequence‐specific oligonucleotide (PCR‐SSO), 36 DNA sequencing‐based typing (PCR‐SBT), 37 matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS), 38 PCR‐single‐base extensions (PCR‐SBE), 39 DNA microarray, 40 next‐generation sequencing, 41,42 droplet digital PCR, 43 and high resolution melting PCR (PCR‐HRM) 44 (Table 1). While PCR‐SSP is the most popular method for HPA‐15 genotyping, current methods may be less time‐consuming, more cost‐effective, and may achieve high‐throughput 45 .…”
Section: Laboratory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a large diversity of HPA genotypes have been reported from varied human ethnic groups from a variety of geographical locations (Azizi et al., 2021; Hayashi et al., 2020; Jovanovic Srzentic et al., 2021; Kazemi et al., 2020; Silva‐Malta et al., 2018; Yan et al., 2006). Many of these studies have suggested significant differences in the frequencies between populations.…”
Section: Introductionmentioning
confidence: 99%